Interobserver Reliability of Radiographic Angles and Measurements in Flat Foot Deformity. Issue 4 (November 2022) - Weigelt, Lizzy; Myatt, Darren; Chapman, James; Philpott, Matthew; Lyle, Shirley; Kelly, Gerry; Kasture, Sarang P.; Heyes, Gavin; Mason, Lyndon W.; Molloy, Andrew P.
Category: Other Introduction/Purpose: Radiographic angles and measurements are widely used in foot and ankle pathologies to define normal and abnormal skeletal alignment. In spite of this the inter-observer reliability of these parameters is debatable. The aim of this study was to determine the inter-observer reliability of various radiographic angles and measurements in flat foot deformity. Methods: Antero-posterior (AP) and lateral foot radiographs of 18 patients with flatfoot deformity were analysed by eight clinicians of various grade of experience (2 consultants, 4 fellows / registrars and 2 core training grades) with 11 different radiological parameters. A digital presentation demonstrating the method of measurement of all parameters using same software was provided to the participants. The inter-observer reliability was analysed using interclass correlation (ICC) model mixed for reliability at 95% confidence interval for individual parameters and different grade of experience. Results: The inter-observer reliability was excellent (>0.9) in calcaneal pitch angle (CPA), medial cuneiform height (C1H) and lateral incongruency angle (LIA). It was good (0.75 - 0.90) in talo-navicular angle (TNA), medial cuneiform articular angle (CAA), medial arch sag angle (MASA), medial cuneiform - 1st MT angle (C1MTA), talonavicular coverage angle (TNCA)andtalar - 1st MT angle on AP radiograph (T1MTA). The inter-observer reliability was moderate (0.5 - 0.75) in Meary's angle and talo-navicular uncoverage percentage (TNUP). The reliability did not differ with the grade of surgeon on sub-group analysis. Conclusion: This is first study to analyse the interobserver reliability of radiographic measurements in a flatfoot deformity, including grade of surgeon. The results suggest that these radiological parameters can be reliably used in clinical practice if standard measurement techniques are followed by clinicians of all grades.